(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The decision of choosing a career is a pivotal point in students’ life and could significantly impact personal satisfaction, financial stability, and overall well-being students of today face increasingly complex landscape of career options, making the process of career choice more challenging and daunting. It is against this backdrop that the study investigated parental involvement as correlates of career decision-making among secondary school students in Oyo State, Nigeria. Descriptive survey research design of correlational types was adopted in the study and the population of the study included 371, 040 secondary school students in Oyo State. The sample size was 384 secondary school students which was determined using Krejcie and Morgan sample size determination table. Questionnaire was the instrument used in the collection of data and data were analysed using simple percentage, Pearson product moment correlation (PPMC) and simple regression at 0.05 level of significance. Results revealed that there was significant positive relationship between parental involvement and career decision-making (r = 0.503, p<.05). There was a significant influence of parental involvement and career decision-making, (F (1, 382) = 66.484, p<0.05), and parental involvement contributed 10.6 to the prediction of career decision-making. It was concluded that parents have a strong influence over the choices of career decision that their children make. It was recommended that giving negative comments about different careers by parents should be avoided. This is because children are susceptible to careless comments parents make about good and bad professions as this could make them to lose interest in their dream careers.